2018
DOI: 10.1021/acs.jpcb.7b10913
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Mechanisms of Cu2+-Doped Na2O–Al2O3–SiO2 Glasses during Heating in H2 Gas

Abstract: Controlling valence state of metal ions that are doped in materials has been widely applied for turning optical properties. Even though hydrogen has been proven effective to reduce metal ions because of its strong reducing capability, few comprehensive studies focus on practical applications because of the low diffusion rate of hydrogen in solids and the limited reaction near sample surfaces. Here, we investigated the reactions of hydrogen with Cu-doped NaO-AlO-SiO glass and found that a completely different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Recently, Nogami et al reported the hydrogen diffusion coefficient through sodium aluminosilicate glasses (Na2O-Al2O3-SiO2) prepared by the melt-quenching technique. 34 The diffusion coefficients of hydrogen at 400-600 °C estimated for this glass with an Al/Na atomic ratio <1 were 10 −16 -10 −15 m 2 s −1 order; as a typical example, the diffusion coefficient at 500 °C estimated for 20Na2O•10Al2O3•70SiO2 glass was 1.8 × 10 −15 m 2 s −1 . 29 In this study, as listed in Table 4, the D(Free) at 500 °C estimated for non-doped amorphous silica was 6.1 × 10 −15 m 2 s −1 .…”
Section: Si-oh/od Conversion Behaviorsmentioning
confidence: 81%
“…Recently, Nogami et al reported the hydrogen diffusion coefficient through sodium aluminosilicate glasses (Na2O-Al2O3-SiO2) prepared by the melt-quenching technique. 34 The diffusion coefficients of hydrogen at 400-600 °C estimated for this glass with an Al/Na atomic ratio <1 were 10 −16 -10 −15 m 2 s −1 order; as a typical example, the diffusion coefficient at 500 °C estimated for 20Na2O•10Al2O3•70SiO2 glass was 1.8 × 10 −15 m 2 s −1 . 29 In this study, as listed in Table 4, the D(Free) at 500 °C estimated for non-doped amorphous silica was 6.1 × 10 −15 m 2 s −1 .…”
Section: Si-oh/od Conversion Behaviorsmentioning
confidence: 81%
“…According to the model, the layer thickness, X, can be obtained as a function of heating time, t, as shown in the following Equation 1: X=(2pKt/Cx) 1/2 =(4D*t) 1/2 (1) where K is the permeation of the H 2 gas, D* is the apparent diffusion coefficients of the H 2 gas, p is the H 2 pressure, and Cx is the Cu ions concentration of reaction sites [18][19][20][21].…”
Section: Reduction Processmentioning
confidence: 99%
“…79,80 Additionally, the presence of hydrogen in annealing gas has been found to promote the reduction of dopants in silica glasses. [81][82][83][84] An alternative source of B is found in the reaction we propose could occur in the presence of hydrogen (Equation 2) that produces water which would readily evaporate under the presented reaction conditions. This reaction provides B while providing an explanation for the observed weight-loss.…”
Section: Diffusion-based Dopingmentioning
confidence: 99%